Legitimacy of Account Blocking by Third Parties in the Human Rights Paradigm - Khofidhotur Rovida; Izzah Khalif Raihan Abidin; Hervina Puspitasari (Simbur Cahaya, 2026)
Account blocking by third parties, such as the Financial Transaction Reports and Analysis Centre (PPATK), is a crucial issue within the human rights (HAM) paradigm because it restricts individual ownership rights and economic freedom. This study aims to analyse the legitimacy of account blocking without a court decision and to examine PPATK's legal standing among customers, banks, and law enforcement officials. Using a normative juridical method with a statutory and conceptual approach, this study finds that the PPATK does not have attributive authority to block accounts directly but rather has the authority to request a "temporary suspension of transactions" from financial service providers. As a key finding, this study identifies four parameters for assessing the legitimacy of blocking and ensuring it does not violate human rights: the principles of legality, necessity, proportionality, and procedural justice (due process of law). The analysis indicates that the policy of blocking passive (dormant) accounts solely based on administrative status, without any indication of criminal activity, exceeds its authority and contradicts the principles of legality and consumer protection. Therefore, this study recommends applying the Regulatory Impact Assessment (RIA) instrument in formulating blocking policies to ensure transparency, accountability, and a balance between eradicating financial crimes and protecting citizens' basic rights.